Perlindungan Hukum terhadap Pengguna Instagram dari Maraknya Ancaman Peretasan - Ketut Putri Maharani (Lembaga Pengembangan Kinerja Dosen, 2025)
In recent years, there have been more and more cases of misuse of social media accounts, especially Instagram, through hacking carried out by individuals for illegal purposes. These hacks often involve using the victim's account for fraudulent actions, such as requesting money via the direct messaging feature to the account's followers. This problem raises a number of legal questions, including how the law regulates hacking and fraud on social media platforms such as Instagram, as well as the types of criminal sanctions that can be imposed on perpetrators. This research uses a normative legal approach to analyze existing regulations, especially the Information and Electronic Transactions Law (UU ITE). Based on the ITE Law, hacking is defined as an illegal activity to access, take or transfer electronic system data without permission, which can be subject to criminal penalties in the form of imprisonment and/or fines. In addition, if hacking is followed by fraud, the perpetrator can be charged with additional articles related to fraud as regulated in the Criminal Code (KUHP). This research also highlights the important role of social media organizers in protecting users through developing security features such as data verification. It is hoped that the results of this research can contribute to strengthening legal protection for social media users in the digital era.